Blockchain empowering digital economy - Yang, Yan; Wang, Bin; Zou, Jun (World Scientific/China Machine Press, 2021)
"Big data has been upgraded to our national strategy and has become a catalyst for national and local economic development. With the further promotion of big data and artificial intelligence (AI), the new business model needs to optimize and upgrade. The integration of the blockchain industry will fully implement the digital China strategy and promote the application of big data in China. This unique compendium gives a comprehensive understanding of the blockchain content through the path of technological innovation. It enables readers to fully understand the role of blockchain in promoting the digital economy. The volume will be a useful reference guide for relevant personnel in state ministries and commissions, state-owned enterprises, big data, AI, as well as teachers, researchers and students in higher education institutions"--
Keywords: Blockchains (Databases) / China; Big data / China; Big data; Blockchains (Databases); China